2011
DOI: 10.1007/s00330-011-2269-1
|View full text |Cite
|
Sign up to set email alerts
|

Prostate MRI: diffusion-weighted imaging at 1.5T correlates better with prostatectomy Gleason grades than TRUS-guided biopsies in peripheral zone tumours

Abstract: • Prostate cancer aggressiveness is probably underestimated and undersampled by routine ultrasound-guided biopsies. • Diffusion-weighted MR images show good linear correlation with prostate cancer aggressiveness. • DWI information may be used to improve risk-assessment in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 46 publications
(58 reference statements)
9
65
0
1
Order By: Relevance
“…15,32 The diffusion properties of a biological tissue are related to the amount of interstitial free water and permeability, reflecting tissue cellularity and the presence of intact cellular membranes. In general, cancer, abscesses, fibrosis, hemorrhage and cytotoxic edema may show restricted diffusion compared to than normal tissue, because of the high cellular density.…”
Section: Diffusion-weighted Imaging (Dwi)mentioning
confidence: 99%
See 3 more Smart Citations
“…15,32 The diffusion properties of a biological tissue are related to the amount of interstitial free water and permeability, reflecting tissue cellularity and the presence of intact cellular membranes. In general, cancer, abscesses, fibrosis, hemorrhage and cytotoxic edema may show restricted diffusion compared to than normal tissue, because of the high cellular density.…”
Section: Diffusion-weighted Imaging (Dwi)mentioning
confidence: 99%
“…In prostate cancer (particularly in the peripheral zone, more frequently studied), normal glandular architecture is disrupted and replaced by aggregated cancer cells and fibrotic stroma, which constitutes an inhibitory environment to the movement of water. 16,32,33 The differences in water diffusion rates between normal and tumoral tissues can be depicted and quantitatively represented by apparent diffusion coefficient (ADC) maps, which are obtained with at least two b values. Restricted diffusion typically seen in prostate cancer leads to high signal on raw high b value DWI and low signal intensity on ADC maps (Fig.s 3b-c, 4c-d, 5c).…”
Section: Diffusion-weighted Imaging (Dwi)mentioning
confidence: 99%
See 2 more Smart Citations
“…(22)(23)(24)26,27) Bittencourt et aland Yagci et al showed that the findings of DWI MRI correlate well with GS from prostatectomy specimen rather than biopsy specimen. (6,8) In general prostatectomy is performed in localized or locally advanced PC. PC positive DWI MRI findings (p=0.0059) and a high GS (8 or more) (p=0.0051),was associated with locally advanced PC which suggests that DWI MRI has positive result for PC with high malignancy.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%